2017
DOI: 10.1111/jcal.12168
|View full text |Cite
|
Sign up to set email alerts
|

Three interaction patterns on asynchronous online discussion behaviours: A methodological comparison

Abstract: An asynchronous online discussion (AOD) is one format of instructional methods that facilitate student-centered learning. In the wealth of AOD research, this study evaluated how students' behavior on AOD influences their academic outcomes. This case study compared the differential analytic methods including web log mining, social network analysis and content analysis which were selected by three interaction patterns: person to system (P2S), person to person (P2P) and person to content (P2C) interaction. Forty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
21

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 46 publications
3
35
0
21
Order By: Relevance
“…Second, the multifaceted depiction of varied prestige has provided a rich picture of the participation gap that merits further investigation. Earlier research has found social participation in online forums predictive of learning performance (Jo et al, 2017;Joksimović, Gašević, Kovanović, Riecke, & Hatala, 2015;Russo & Koesten, 2005) and low-performing students more likely to connect with similarly low-performing peers (Dawson, 2010;Hu & Zhao, 2016). This study provides detailed depiction of the participation gap.…”
Section: Scholarly Significance Of Investigating Network Prestige Andmentioning
confidence: 82%
See 4 more Smart Citations
“…Second, the multifaceted depiction of varied prestige has provided a rich picture of the participation gap that merits further investigation. Earlier research has found social participation in online forums predictive of learning performance (Jo et al, 2017;Joksimović, Gašević, Kovanović, Riecke, & Hatala, 2015;Russo & Koesten, 2005) and low-performing students more likely to connect with similarly low-performing peers (Dawson, 2010;Hu & Zhao, 2016). This study provides detailed depiction of the participation gap.…”
Section: Scholarly Significance Of Investigating Network Prestige Andmentioning
confidence: 82%
“…Studies of learner participation in online discussions have benefited from multiple methodologies (Jo et al, 2017). A wide range of methodological approaches, such as Social Network Analysis, Content Analysis, and Regression Analysis, have been applied to studying student participation and its contributing factors.…”
Section: Methodological Approaches To Investigating Participation In mentioning
confidence: 99%
See 3 more Smart Citations